Impact of Pharmaceutical Compounds in the Bioremediation of Municipal Biosolids by the White-Rot-Fungi Trametes hirsuta - Saibi, Sabrina; Haroune, Lounès; Savary, Olivier; Bellenger, Jean-Philippe; Cabana, Hubert (Frontiers in Fungal Biology, 2022)
The potential of microorganisms for the treatment of municipal biosolids is continuously growing. The present studies evaluated the potency of Trametes hirsuta for the reduction in biosolid mass, production of extracellular enzymes, and removal of pharmaceutical compounds (PhACs) in biosolid slurry in the presence and absence of spiked PhACs (5 non-steroidal anti-inflammatories (NSAIs) and 2 psychoactive compounds (PACs)). Toxicity after 35 days of fungal treatment was also assessed. Results showed that the growth of T. hirsuta is limited above 25% and wholly inhibited above 50% of biosolids in the slurry. At 12% of biosolid concentration, biosolid mass was reduced by 90%, NSAIs were entirely removed, but PACs’ removal was only 20%. Increasing biosolid content to 25% did not markedly affect biosolid reduction but significantly enhanced the removal of PACs (> 50%). Results also showed that both PhACs and biosolids induced the production of oxidative enzymes. In 12% biosolids in the slurry, the oxidative potential measured by the ABTS assay (OABTS) reached 5000 mM of OABTS in the presence of PhACs, and 2500 mM of OABTS without PhACs, as compared to 1200 mM of OABTS in control culture. Finally, we report that WRF treatment significantly decreased the toxicity of the biosolids.